Single Event Resolution of Plant Plasma Membrane Protein Endocytosis by TIRF Microscopy - Johnson, Alexander; Vert, Grégory (Frontiers in Plant Science, 2017)
Endocytosis is a key process in the internalization of extracellular materials and plasma membrane proteins, such as receptors and transporters, thereby controlling many aspects of cell signaling and cellular homeostasis. Endocytosis in plants has an essential role not only for basic cellular functions but also for growth and development, nutrient delivery, toxin avoidance, and pathogen defense. The precise mechanisms of endocytosis in plants remain quite elusive. The lack of direct visualization and examination of single events of endocytosis has greatly hampered our ability to precisely monitor the cell surface lifetime and the recruitment profile of proteins driving endocytosis or endocytosed cargos in plants. Here we discuss the necessity to systematically implement total internal reflection fluorescence microcopy (TIRF) in the Plant Cell Biology community and present reliable protocols for high spatial and temporal imaging of endocytosis in plants using clathrin-mediated endocytosis (CME) as a test case, since it represents the major route for internalization of cell-surface proteins in plants. We developed a robust method to directly visualize cell surface proteins using TIRF microscopy combined to a high throughput, automated and unbiased analysis pipeline to determine the temporal recruitment profile of proteins to single sites of endocytosis, using the departure of clathrin as a physiological reference for scission. Using this ‘departure assay’, we assessed the recruitment of two different AP-2 subunits, alpha and mu, to the sites of endocytosis and found that AP2A1 was recruited in concert with clathrin, while AP2M was not. This validated approach therefore offers a powerful solution to better characterize the plant endocytic machinery and the dynamics of one’s favorite cargo protein.